PERGESERAN PELAKSANAAN UPACARA ADAT PERKAWINAN SUKU TIOCIU PADA MASYARAKAT TIONGHOA DI KELURAHAN PARIT TOKAYA KECAMATAN PONTIANAK SELATAN KOTA PONTIANAK - NIM. A1011191274, MARIA VIONITA (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractThe traditional marriage ceremony is one of the customs of the Chinese community in Pontianak City. The stages of the traditional wedding ceremony of the Chinese TioCiu tribe are proposal, determining the date and auspicious days, sangjit, decorating the bridal room and the procession of putting on bed linen, tea pie, wedding reception, returning home on the third day to the parents' house. The stages that shift are not determining an auspicious date and day, not returning to your parents' house on the third day after the wedding not decorating the bridal room, and not putting up bed linen. Formulation of the research problem